THE METHOD OF ASSESSING THE PSYCHO-FUNCTIONAL STATUS OF STUDENTS USING THE METHOD OF GAS DISCHARGE PHOTOGRAPHY OF THE FINGERS OF THE HANDS - Ханюков, Олексій; Пісоцька, Людмила; Короленко, Ганна; Щукіна, Олена (SWorldJournal, 2023)
Introduction. In modern conditions of modernization of the educational process in university education, with the predominance of distance learning methods and the active use of electronic media, there is a great risk of increasing psycho-emotional stress